Eat your greens, reds, yellows, and purples - Mitchem, James; Love, Carrie; King, Dave (Photographer) (DK Publishing, 2016)
"A tasty guide to colorful food, Eat your greens, reds, yellows, and purples is packed with tasty, healthy vegetarian recipes and information on which ingredients are good for you and why"--Page [4] of cover.